Effect of acid solution on some Physical and Mechanical Properties of (Epoxy/polysulphide) Blends - Adnan R. Ahmed (Tikrit Journal of Pure Science)
The aim of present investigation is to evaluate the mechanical properties , (tensile, impact, and hardness) properties and physical properties. Acid absorption for (epoxy/polysulphide) specimens were prepared by open molding technique , with different ratios (95-5),(90-10),(85-15), and (80-20)% weight ratio.